Exploring the impact of emotional intelligence on university academics’ job performance - Omar, Muhd Khaizer; Mohd Puad, Mohd Hazwan; Liu, Sijia (Scientific Research Publishing, 2024)
Thriving in a challenging educational environment requires leaders to go beyond traditional leadership roles. Leaders should possess a strong mindset and the ability to control their emotions, which ultimately improves organizational job performance. Although emotional intelligence is recognized as a critical factor impacting job performance across various industries, its specific impact on the higher education sector is considerably less attentive. This study used a quantitative survey approach to examine the emotional intelligence of university academics and its effects on their work performance. The survey included 293 respondents from five universities in Henan Province, China. The results showed a significant positive correlation between emotional intelligence and job performance. Research indicates that higher levels of emotional intelligence—including self-awareness, emotion regulation, motivation, empathy, and social skills—are associated with better job performance. This relationship is moderated by personal characteristics, organizational support, and cultural context. These findings highlight the importance of incorporating emotional intelligence into educational leadership and continuous professional development (CPD) and induction training programs for academics, not only to facilitate teaching and learning processes but also to enhance the overall educational ecosystem.